Hard coating films of fluorine-containing ladder-like structured polysilsesquioxane as negative triboelectric materials for high-performance triboelectric generators. (January 2022) - Oh, Hyeontaek; Jo, Euihyun; Jang, Hye Woon; Jung, Hyeongjun; Park, Sang Hyeok; Kim, A Young; Jung, Jong Hoon; Youk, Ji Ho; Lee, Minbaek
Abstract: Triboelectric nanogenerators (TENGs) have attracted considerable attention owing to their versatile potential to meet the needs of renewable energy sources. TENG materials have both electrical and mechanical excellence, considering the common mechanism of contact electrification. In this study, ladder-like structured poly(1H, 1H, 2H, 2H-nonafluorohexyl-co-2-(3, 4-epoxycyclohexyl)ethyltrimethoxy silsesquioxane)s (LPEFSQs) were synthesized as a hard coating material in TENG applications. LPEFSQs contain the UV-curable functional group and halogen elements and can be coated easily on various polymeric films. Such hard coating films of LPEFSQs enhance the electrical and mechanical properties of any polymer substrate. A LPEFSQ-based TENG exhibits superior performance in both aspects than polytetrafluoroethylene, an extreme triboelectric material commonly used as a negative side. In a large-scale demonstration, the open-circuit voltage and short-circuit current outputs reached 1140 V and 23 μ A, respectively. Therefore, this hard coating material will provide a facile but efficient method to increase the electrical performance of TENGs in harsh mechanical environments.